2018 Korean Society of Hypertension Guidelines for the management of hypertension: part II-diagnosis and treatment of hypertension - Lee, Hae-Young; Shin, Jinho; Kim, Gheun-Ho; Park, Sungha; Ihm, Sang-Hyun; Kim, Hyun Chang; Kim, Kwang-il; Kim, Ju Han; Lee, Jang Hoon; Park, Jong-Moo; Pyun, Wook Bum; Chae, Shung Chull (Clinical hypertension, 2019)
The standardized techniques of blood pressure (BP) measurement in the clinic are emphasized and it is recommended to replace the mercury sphygmomanometer by a non-mercury sphygmomanometer. Out-of-office BP measurement using home BP monitoring (HBPM) or ambulatory BP monitoring (ABPM) and even automated office BP (AOBP) are recommended to correctly measure the patient’s genuine BP. Hypertension (HTN) treatment should be individualized based on cardiovascular (CV) risk and the level of BP. Based on the recent clinical study data proving benefits of intensive BP lowering in the high risk patients, the revised guideline recommends the more intensive BP lowering in high risk patients including the elderly population. Lifestyle modifications, mostly low salt diet and weight reduction, are strongly recommended in the population with elevated BP and prehypertension and all hypertensive patients. In patients with BP higher than 160/100 mmHg or more than 20/10 mmHg above the target BP, two drugs can be prescribed in combination to maximize the antihypertensive effect and to achieve rapid BP control. Especially, single pill combination drugs have multiple benefits, including maximizing reduction of BP, minimizing adverse effects, increasing adherence, and preventing cardiovascular disease (CVD) and target organ damage.